The history channel where the past comes alive - Hayes , Chuck; Nash , Bruce; Jaffe Productions; Actuality Productions; History Channel (firm); New Video Group (New York : A&E Television Networks, 1997)
Presentation on the emergence of the stell industry in the United States and how steel shaped the country . The Industrial Revolution wouls not have been possible without steel & the industries it created
Originally broadcast on televisyen as an episode of the program modern marvels
Camera , Jerry Hughes... [et al.] ; graphics , Doug Whitney ; editor , Jane McCord ; narrator , Earl Boen ; music , Alan Ett Mel Weinstein , Tony DeArdo
Speakers : W.A Soffa , Mark Reutter, Daniel Santoro, Mel Weinstein,Tony DeArdo
Keywords: Steel industry and trade -- United States -- History; Industrialization -- United States -- History; Iron industry and trade -- United States -- History